Kemampuan Bioaktif Glass (Novamin) dan Casein Peptide Amorphous Calcium Phosphate (CPP-ACP) terhadap Demineralisasi Enamel - Jeanny Kathleen H; Cecilia G.J. Lunardhi; Ari Subiyanto (Conservative Dentistry Journal, 2017)
Background: Oral cavity is always associated with a dynamic atmosphere where the process of demineralization and remineralization will continue to occur. Caries is a pathological state of continuous demineralization process. Prevention of the occurrence of demineralization process can be done by enhancing remineralization, materials that can be used materials that can trigger a process of remineralization include fluoride, cpp-acp, and novamin. Purpose: The aim of this study was to evaluate and compare the potential of bioactive-Glass (Novamin) and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) containing dentifrice on enamel demineralization. Method: A total of 24 sound human premolars were divided into 4 groups and continued into pH cycling regime to be evaluated with Scanning Electron Microscope – Energy Dispersive X-Ray. Result: Group D showed significantly higher values (P < 0.05) when compared with less demineralization lesion than Group A, B, and C. Conclusions: The ability of Novamin on demineralization lesions better than CPP-ACP.